Protection induced in pigs previously infected by the non-virulent strain 1330 of Streptococcus suis serotype 2 is not due to the secretion of the bacteriocin suicin - Samantha J. Hau; Nahuel Fittipaldi; Servane Payen; Daniel Grenier; Daniel W. Nielsen; Susan L. Brockmeier; Marcelo Gottschalk (PLoS ONE, 2025)
Streptococcus suis is a systemic pathogen of swine and imposes a significant economic burden on the swine industry. Disease with S. suis is controlled with antibiotic treatment and vaccination with inactivated vaccines, which can be derived from the strains circulating on the farm. Inactivated vaccines have shown mixed results with minimal data supporting reductions in morbidity and mortality following their use. With increasing restrictions on antibiotic use and increasing concerns surrounding antimicrobial resistance, alternatives to antibiotics or novel, highly effective vaccines are needed for treating or preventing disease with S. suis. Bacteriocins are a potential alternative to antibiotics, as bacteriocins are antimicrobial peptides produced by bacteria. However, the use of bacteriocins to limit pathogenic S. suis remains relatively under-examined. Live vaccines are a potential novel and effective method of preventing disease, as they provide competition for pathogenic strains and would limit pathogenic strain colonization while stimulating a protective immune response. This study investigated the use of an avirulent, bacteriocin producing isolate of S. suis (90–1330) as an intranasal vaccine and evaluated the role of the bacteriocin by comparing protection to animals inoculated with a mutant lacking bacteriocin production (90–1330Δsuicin). Animals were protected from systemic disease when challenged with a virulent isolate 21 days after inoculation with either 90–1330 or 90–1330Δsuicin but were not protected when challenged 3 days after inoculation. Evaluation of antibody titers showed increased titers 21 days post-inoculation, and the humoral response was likely providing systemic protection. Although 90–1330 was unable to protect animals challenged 3 days post-inoculation, the strain should be considered a good candidate for vaccine development. S. suis 90–1330 was able to induce a protective immune response with a single intranasal inoculation and bacteriocin production may be able to contribute to protection when animals have a lower exposure dose, as in a production setting.